PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN PENDIDIK di MAN 1 KOTA BOGOR - Rania Falah Sungkar; Fahmi Irfani; M Kholil Nawawi (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2022)
This research discusses the role of the school principal in enhancing discipline among educators. The background indicates that educators' discipline is influenced by the role of the principal. The method used in this study is descriptive qualitative, employing observation and interview techniques. The results obtained show that the role of the principal is crucial. Overall, this research emphasizes that the principal plays a key role in fostering discipline among educators. Through effective leadership and appropriate approaches, the principal can create an environment that supports discipline, which in turn will have a positive impact on the quality of education in the school